SISTEM PAKAR DIAGNOSA PENYAKIT SALURAN PERNAFASAN DENGAN METODE FUZZY TSUKAMOTO - Dhevi Dadi Kusumaningtyas; Muhammad Hasbi; Hendro Wijayanto (Jurnal Teknologi Informasi dan Komunikasi (TIKomSiN), 2019)
Respiratory diseases are one of the most common diseases in Indonesia. Respiratory diseases increase the risk of fatal if not treated immediately. However, it is unfortunate that knowledge about the risk of respiratory disease is still lacking. The search method used in making this expert system is forward chaining with binary tree structure. Namely doing the processing of a set of data, then conducted inference in accordance with the rules applied to find the optimal conclusion. Experts provide rules for determining symptoms and illness. While the calculation and ranking of diseases that may suffer patients using the method fuzzy tsukamoto to provide the results of calculations that are certain based on the parameters. Then the patient's diagnostic process is done by the system. The Diagnostic Expert System for Respiratory Disease has been successfully established and can be used to assist in estimating the illness suffered by the patient as the result of the developed system is not much different from the running system. Based on the comparison of disease diagnosis result in expert system with manual system then the system accuracy level is 90,9%. Based on the website view has the largest percentage of 71.42 in good description, for user friendly / ease of respiratory system experts get the largest percentage of 85.71 in good information, to assist in the process of disease information and treatment get the largest percentage of 57.14 in a good description, to help the diagnosis process becomes easier to get the largest percentage of 71.42 in good information, for this expert system provides information on respiratory disease treatment accurately get the largest percentage of 57.14 in either.